PELATIHAN PEMBUATAN BIODIESEL DARI MINYAK JELANTAH SKALA LABORATORIUM DI SMP NEGERI 5 PANGKALAN PANJI BANYUASIN SUMATERA SELATAN - Fatria Fatria; Lety Trisnaliani; Indah Purnamasari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2018)
This community service activity for processing used cooking oil into biodiesel was carried out at Banyuasin III SMPN 5, South Sumatra. Around the school there are many fried traders and tent stalls that have the potential to produce used cooking oil. Seeing this potential, the community service team of the Sriwijaya Polytechnic Department of Chemical Engineering provided training to students and teachers of the South Sumatra Banyuasin SMPN 5 to make laboratory-scale biodiesel from used cooking oil. Biodiesel production can be used to increase the potential of human resources and preserve the environment from used cooking oil pollutants. The method of implementing this service activity is with the pattern of field schools with press points on the exploration of knowledge, awareness of the environment, and skills and forms of approach taken to increase the motivation of students and teachers as partners and able to process used cooking oil into biodiesel by socializing about the importance of saving fossil fuels, protecting the environment and producing alternative fuels from used cooking oil which are often found in everyday life.